2005
DOI: 10.1007/s10637-005-1444-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of CCI-779 in patients with recurrent glioblastoma multiforme

Abstract: CCI-779 was well tolerated at this dose schedule; however, there was no evidence of efficacy in patients with recurrent GBM. Despite initial disease stabilization in approximately 50% of patients, the durability of response was short. Because of the low toxicity profile, CCI-779 may merit exploration in combination with other modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
195
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(197 citation statements)
references
References 18 publications
1
195
0
1
Order By: Relevance
“…Notwithstanding the lower 5 mg dose administered in this study, the types of adverse events observed were not dissimilar to those seen in studies of temsirolimus in patients with cancer, although a greater percentage of cancer patients had thrombocytopaenia, rash, and mucositis (Atkins et al, 2004;Hidalgo et al, 2006) than did the healthy subjects in this study. Previous studies have suggested that the incidence and severity of some adverse events are proportional to the exposure to temsirolimus (Boni et al, 2005;Chang et al, 2005). In a population PK safety analysis of patients receiving 25, 75, or 250 mg of temsirolimus weekly, clinically interesting associations between AUC sum and adverse event severity were observed for thrombocytopaenia (P ¼ 0.007), pruritus (P ¼ 0.011), and hypertriglyceridaemia (P ¼ 0.040) (Boni et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Notwithstanding the lower 5 mg dose administered in this study, the types of adverse events observed were not dissimilar to those seen in studies of temsirolimus in patients with cancer, although a greater percentage of cancer patients had thrombocytopaenia, rash, and mucositis (Atkins et al, 2004;Hidalgo et al, 2006) than did the healthy subjects in this study. Previous studies have suggested that the incidence and severity of some adverse events are proportional to the exposure to temsirolimus (Boni et al, 2005;Chang et al, 2005). In a population PK safety analysis of patients receiving 25, 75, or 250 mg of temsirolimus weekly, clinically interesting associations between AUC sum and adverse event severity were observed for thrombocytopaenia (P ¼ 0.007), pruritus (P ¼ 0.011), and hypertriglyceridaemia (P ¼ 0.040) (Boni et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Results have been reported from studies in metastatic breast (MBC), renal cell (RCC), 75 small cell lung, (SCLC), 76 endometrial carcinoma, 77 mantle cell lymphoma (MCL), 78 melanoma, 79 and glioblastoma multiforme (GBM). 80,81 The results of these studies are summarized in Table 2. The most promising activity has been seen in mantle cell lymphoma and endometrial carcinoma with objective tumor response rates of 30-40%.…”
Section: Temsirolimus (Cci-779)mentioning
confidence: 99%
“…In glioblastoma, attempts to target mTOR with rapamycin and its analogues have largely failed to show efficacy (7)(8)(9), mediated by difficulty in fully inhibiting mTORC1 signaling and by emergence of a feedback loop, that activates pro-growth, pro-survival Akt signaling (10). Rapamycin analogues also activate MAPK through a PI3K-dependent mechanism in other cancer types, suggesting additional potential mechanisms of clinical resistance and raising the need for alternative strategies to target mTOR signaling in patients (11).…”
mentioning
confidence: 99%